SOCIALIZATION TO TEENAGERS REGARDING THE LEGAL ASPECTS OF BULLYING BEHAVIOR ON SOCIAL MEDIA - Hidayati, Taufika (Universitas Negeri Medan, 2024)
Bullying is threatening, mocking or annoying behavior carried out by a person or group of people intentionally towards someone who is weaker. This action is generally carried out only for personal satisfaction. Along with the development of technology, bullying is now carried out using social media or cyberbullying. It will allow more people to see and imitate the behavior. If this action is carried out continuously or excessively, it will have an impact on the victim, such as experiencing mental disorders, depression and even suicide. Because of its bad impact, bullying can still be prevented and overcome because bullying is an action based on the perpetrator's choice. Bullying behavior is rampant among teenagers, especially middle schools. Providing understanding to teenagers is very influential in prevention efforts. The aim of this community service is to provide education, insight and better understanding to students. The result of this activity was to build Anti-Bullying students’ awareness. The method used in this activity was to provide education by delivering material by showing videos that include definitions, types, legal traps and the impact of victims of bullying behavior, which is then closed by question and answer session to teenagers.